Análise da indústria de seguros brasileira a partir do modelo Estrutura-Conduta-Desempenho (ECD): 2003/2020 - Fabrício Zacchè Siqueira; Álvaro Alves de Moura Jr. (Revista de Economia Mackenzie, 2022)
The insurance sector, open supplementary pension and capitalization sector has shown great advances in the supply of new products and services from 2003 to 2020, and consistently showing a growth in the volume of revenues and their participation in the national economy. From the perspective of efficient resource allocation, long-term savings and risk management, the insurance market has also been contributing to greater efficiency and economic growth in the national financial sector. In this sense, the purpose of this paper is to present a sector analy-sis of the insurance market in Brazil. Therefore, the work will be carried out based on the Structure- Conduct-Performance (SCP) model. Among the main results of the research, it is noteworthy that the sector is classified as a low-concentration oligopoly, as well as has high barriers to entry associated, mainly, with the national regulatory system; in terms of conduct, current innovations are affecting both the structure and performance of the insurance market, in addition to the recent growth in mergers and acquisitions operations; finally, it is worth highlighting the high financial results of the sector in recent years analyzed.